Increasing Knowledge About the Dangers of Pornography on Adolescent Brain Development in Students of SMA Negeri 1 Sungai Pinang, Ogan ilir Regency - Mareta Akhriansyah; Raden Surahmat; Nuriza Agustina (PT FORMOSA CENDEKIA GLOBAL, 2022)
The development of adolescent behavior is influenced by various factors of knowledge, attitude and exposure to sources of information. Conditions Adolescent sexual behavior is increasingly faced with exposure to pornography which continues to threaten, especially with easy access in various media to sources of pornography and the influence of association. This community service activity is carried out to increase knowledge and insight to students and teachers about the dangers of pornography in adolescent brain development. The activity was carried out using the counseling method for SMAN 1 Sungai Pinang students about the impacts and dangers of pornography using power point media. In addition, participants were given a leaflet containing a summary of the accompanying material. The activity was carried out for 30 participants in September 2022. The results of the activity had a positive impact on student knowledge after the assessment before (68) and after the activity (83.3), there was an average increase in student knowledge of 15.3%. The importance of increasing behavior in terms of knowledge and the presence of positive information on adolescent knowledge regarding the dangers of pornography is always being increased by involving health workers or related parties so that they can maintain adolescent behavior in a more positive direction.